Relax : Parking Avenir : a case study. - Künstlerhaus Bethanien Berlin; Baumann, Leonie; Gohlke, Gerrit; Höge, Helmut; Tannert, Christoph (Berlin : Künstlerhaus Bethanien Berlin, 2003)
Parking Avenir is a case study of art's closeness to life and at the same time an anthology about Berlin's legendary district, Kreuzberg. The book not only uses more than 150 newspaper clippings, letters, and pamphlets borrowed from archives to tell the story of Mariannplatz, a center of alternative political culture sung in songs. It also depicts this place, in the example of the Künstlerhaus Bethanien, as the site of a productive problematical relationship between art and the world. In documents, video images, and essays, Parking Avenir tells about Kreuzberg as seen by art. And thus becomes a story about the state of art.
biog. 1 p.
Duits
Engels
Exhibition. Relax : Parking Avenir. Künstlerhaus Bethanien Berlin. 2003-11-07. 2003-11-23
boek
Keywords: Relax; Berlijn